La duplicación de funciones y posiciones de parentesco como estrategia para la construcción de la paternidad/maternidad en las familias reconstituidas - Jociles Rubio, María Isabel; Villaamil Pérez, Fernando (Pontificia Universidad Católica del Perú. Fondo Editorial, 2008)
It is interesting to notice that authors such as Théry (1985), le Gall and Marin (1993) and le Gall (1996) who study reconstituted families have not dealt with all of the possible consequences of the idea of family constellation, specially the one which states that the concept of family should include more than just residency. Another point to notice is that the paternity and maternity analysis hasn’t been applied within the family modality. This article presents the results of an investigation where this idea has proven to be very successful in analysing the ways in which father/mother and stepfather/stepmother parental positions and roles are formed in the basis of these families, given that the ways in which the role or parental position of a biological father without custody is formed is not independent from other ways in which a stepfather manages to build his parental position, just like during these processes members of the family constellation also have some influence, such as the spouses’s or couple’s parents.

Llama la atención que autores como Théry (1985), Le Gall y Martin (1993) y Le Gall (1996) no hayan extraído, en sus estudios sobre las familias reconstituidas, todas las consecuencias posibles de la idea de constelación familiar, en especial la que sostiene que el concepto de familia debe extenderse más allá de la residencia. Y llama asimismola atención que no la hayan aplicado al análisis de la paternidad y la maternidad dentro de esta modalidad de familias. En la investigación cuyos resultados se presentan en este artículo, dicha idea se ha mostrado muy fructífera para examinar los modos a través de los cuales se construyen el rol y la posición parental de los padres/madres y padrastros/madrastras en el seno de estas familias. Esto ocurre porque las formas en que se construye, por ejemplo, el rol/la posición paternal de un padre biológico no custodio no es independiente de aquellas otras en que se ha construido y/o se está construyendo el rol/la posición parental del padrastro, de igual manera que en esos procesos pueden tener también una incidencia fundamental las prácticas de otros miembros de esas constelaciones familiares, como los padres de los distintos cónyuges/parejas que las integran.
The duplication of functions and kinship positions as a strategy for the construction of paternity / maternity in reconstituted families
Keywords: Familias reconstituidas; Constelación familiar; Paternidad; Maternidad; Roles; https://purl.org/pe-repo/ocde/ford#5.04.03